THE EFFECT OF SOCIAL MEDIA USE AND BUSINESS CAPITAL ON MSMEs PERFORMANCE IN THE DIGITAL ERA : PENGARUH PENGGUNAAN MEDIA SOSIAL DAN MODAL BISNIS TERHADAP KINERJA UMKM DI ERA DIGITAL - Frisca Felicia; Fenny Afrida (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the influence of Social Media Utilization and Business Capital on the Performance of Micro, Small, and Medium Enterprises (MSMEs). This study uses a quantitative approach with primary data collected from 230 MSME respondents through questionnaires. The results of the validity and reliability tests indicate that the research instruments used are valid and reliable. Multiple linear regression analysis shows that the Business Capital variable has a positive and significant effect on MSME Performance, while Social Media Utilization does not have a significant effect. The results of the partial test (T-Test) show that Social Media Utilization (Sig. value 0.605) has no significant effect, while Business Capital (Sig. value 0.000) individually has a significant effect on MSME Performance. Simultaneously (F-Test), both variables have a significant effect with a Sig. value of 0.000. The coefficient of determination (R²) value of 0.421 indicates that 42.1% of the variation in MSME performance can be explained by the use of social media and business capital, while the remaining 57.9% is explained by other factors outside this research model. Keywords:Utilization of Social Media, Business Capital, MSME Performance